Assessing the Perceptibility of Prehistoric Monuments on their Landscape. An Exploratory Approach Using Agent-Based Modelling (Vegueta: Anuario de la Facultad de Geografía e Historia, 2023)
The perceptibility of a prehistoric monument (the property of being perceptible from its surrounding landscape) can be quite difficult to analyse by means of traditional static models. Such difficulty lies in the fact that perceptibility depends upon many other factors beyond simple topographical position, such as size, colour, contrast with the surroundings or even the specific circumstances of the audience, many such circumstances being of an immaterial nature. In this paper, we explore the potential use of Agent-Based Modelling for the analysis of archaeological perceptibility.